A case series and review of sporotrichosis in Sikkim - Pema Yoden Bhutia; Shrijana Gurung; Prakash Peralam Yegneswaran; Jagat Pradhan; Uttam Pradhan; Tshering Peggy; Prakash Kumar Pradhan; Chewang Doma Bhutia (Journal of Infection in Developing Countries)
Sporotrichosis caused by the fungus Sporothrix schenckii has been widely reported from the northern Himalayan belt and the north eastern region of India. Three autochthonous cases of lymphocutaneous sporotrichosis from east and south districts of Sikkim are reported. Fluid aspirate from the nodulo-ulcerative lesions were sent for cytology and fungal culture. S. schenckii was isolated on culture and cytological examination in all three cases showed granulomatous reaction. Thermal dimorphism was demonstrated and animal pathogenicity testing was performed. Saturated solution of potassium iodide was used for treatment and the last case was treated with itraconazole and potassium iodide. Awareness of this disease and an extensive environmental study is required to understand the actual burden of this disease.